Value Co-Creation An Exploratory Study of Sagala Multi-Brand Virtual Kitchen - Jurry Hatammimi; Tediany Dwi Amiranti (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
Culinary businesses accounted for 40% of Indonesian MSMEs at the height of the COVID-19 pandemic, making them one of the most affected industries. The transformation of the business model into a cloud kitchen or virtual kitchen is one of the innovation methods that can benefit the post-pandemic situation. This business model is thought to offer a value co-creation strategy. The authors note that Sagala, one of the virtual kitchens, has both a strong future and a low entry barrier. In order to analyze and assess Sagala's value co-creation, this study will employ The DART approach. Interviews with individuals from the staff, delivery, and customer categories were done as part of this exploratory study. Furthermore, the results show that Sagala's value co-creation initiative is a success, but conversation, particularly with delivery personnel, still has to be enhanced. Therefore, it is advised to create a framework to accept complaints and suggestions from both customers and delivery personnel. It is advised to create the value co-creation mechanism for the cloud kitchen company as further research.